"Global transformation and the third world / edited by Robert O. Slater, Barry M. Schutz and Steven R. Dorr" - "Slater, Robert O. (ed.)" (London, 1993)
In December 1990, the editors of this volume were privileged to bring together a group of internationally distinguished scholars to discuss the dramatic changes in global politics and their effect on what we euphemistically label the third world.
Keywords: Democracy Developing Countries